2015
DOI: 10.3126/jmmihs.v1i4.12000
|View full text |Cite
|
Sign up to set email alerts
|

Nepalese Trekking Guides: A Quantitative Study of Sexual Health Knowledge And Sexual Behaviour

Abstract: Tourism, a global industry, brings with it a number of public health problems, one of which is the spread of sexually transmitted infections transmitted between travellers and hosts. Previous studies have largely focused on sex workers and sex tourists. This study assesses sexual behaviour, knowledge and condom use among male trekking guides in Nepal. A self-administered questionnaire survey (n=324) was conducted using snowball sampling amongst men working as mountain trekking guides in Nepal. Most respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…For example, a country-based Nepal Demographic Health Survey (NDHS) indicated that 40 % of young women and 24 % of young men had their first sex by age 18 [13]. Similarly, a recent study reported that 59 % of men had initiated sex before the age of 18 [14]. Further, a study among returnee migrant workers in Nepal revealed that 40 % of the participants had their sexual debut between 15 and 19 years of age, while 10 % reported their sexual debut to be <15 years [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a country-based Nepal Demographic Health Survey (NDHS) indicated that 40 % of young women and 24 % of young men had their first sex by age 18 [13]. Similarly, a recent study reported that 59 % of men had initiated sex before the age of 18 [14]. Further, a study among returnee migrant workers in Nepal revealed that 40 % of the participants had their sexual debut between 15 and 19 years of age, while 10 % reported their sexual debut to be <15 years [15].…”
Section: Introductionmentioning
confidence: 99%